Fiber-wireless convergence in next-generation communication networks : systems, architectures, and management - Tornatore, Massimo; Chang, Gee-Kung; Ellinas, Georgios (Springer, 2017)
This book investigates new enabling technologies for Fi-Wi convergence. The editors discuss Fi-Wi technologies at the three major network levels involved in the path towards convergence: system level, network architecture level, and network management level. The main topics will be: a. At system level: Radio over Fiber (digitalized vs. analogic, standardization, E-band and beyond) and 5G wireless technologies; b. Network architecture level: NGPON, WDM-PON, BBU Hotelling, Cloud Radio Access Networks (C-RANs), HetNets. c. Network management level: SDN for convergence, Next-generation Point-of-Presence, Wi-Fi LTE Handover, Cooperative MultiPoint." Addresses the Fi-Wi convergence issues at three different levels, namely at the system level, network architecture level, and network management level " Provides approaches in communication systems, network architecture, and management that are expected to steer the evolution towards fiber-wireless convergence " Contributions from leading experts in the field of Fiber-Wireless Convergence.
Keywords: Wireless communication systems.; Optical fiber communication.; elektronické knihy; electronic books